2010
DOI: 10.1021/la100272y
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite Growth Inhibition by Osteopontin Hexapeptide Sequences

Abstract: The effects of three acidic hexapeptides on in vitro hydroxyapatite growth were characterized by pH-stat kinetic studies, adsorption isotherms, and molecular modeling. The three peptides, pSDEpSDE, SDESDE, and DDDDDD, are equal-length model compounds for the acidic sequences in osteopontin, a protein that inhibits mineral formation in both calcified and noncalcified tissues. Growth rates from 1.67 mM calcium and 1.00 mM phosphate solution were measured at pH 7.4 and 37 degrees C in 150 mM NaCl. pSDEpSDE was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…In addition, our MD suggests that the minimal distance between the crystal surface and the peptide is a relevant aspect regarding the ability of HA growth inhibition. A similar study, using phosphorylated and unphosphorylated osteopontin hexapeptides, observed that the phosphorylated hexapeptide had a strong growth inhibitor effect, whereas its unphosphorylated sibling showed no growth-inhibitory function (Silverman et al 2010). Furthermore, the degree of phosphorylation of osteopontin affects its potential as an inhibitor, possibly as a biological switch to turn its inhibitor function "on or off" (Azzopardi et al 2010;Baht et al 2010;Grohe et al 2007).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, our MD suggests that the minimal distance between the crystal surface and the peptide is a relevant aspect regarding the ability of HA growth inhibition. A similar study, using phosphorylated and unphosphorylated osteopontin hexapeptides, observed that the phosphorylated hexapeptide had a strong growth inhibitor effect, whereas its unphosphorylated sibling showed no growth-inhibitory function (Silverman et al 2010). Furthermore, the degree of phosphorylation of osteopontin affects its potential as an inhibitor, possibly as a biological switch to turn its inhibitor function "on or off" (Azzopardi et al 2010;Baht et al 2010;Grohe et al 2007).…”
Section: Discussionmentioning
confidence: 93%
“…The crystalline phase in the referenced study was mostly apatite, together with whitlockite, which was only detected by using a very intense X-ray source such as synchrotron radiation. Promoters, inhibitors, and templates of crystallization are omnipresent in physiological and pathological biomineralization processes (7,8,22,25,34). The structure of the deposits gives some clues about the precipitation conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the deposits gives some clues about the precipitation conditions. Actually, the role of inhibitors in preventing mineralization in noncalcifying tissues is generally assumed (22), whereas the lack of inhibitors is considered an important risk factor for pathological calcifications (34). Live cell deposits show similar macroscopic and microscopic structures.…”
Section: Discussionmentioning
confidence: 99%
“…The study led to the identification of phosphorylated hexapeptide "pSDEpSDE" (the codename H8V used further in the text), as the most potent calcium growth inhibitor and thus as one possible OPN active site. [7] Therefore, we decided to investigate the structural and thermodynamic aspects of U VI coordination with the phosphorylated H8V peptide by combining thermodynamics and spectroscopic techniques. Sutton and Burastero [8] described the speciation of U VI ions in biological fluids, thus showing that acidic and fairly acidic conditions can be chosen to simplify U VI speciation and limit U VI hydrolysis.…”
Section: Introductionmentioning
confidence: 99%